Mind Matters in Children - Lyen, Kenneth (Singapore : World Scientific Publishing Co. Pte. Ltd, 2023)
This book delves into both the normal as well as the abnormal functioning of a child's mind. Topics covered include intelligence, creativity, consciousness, memory and normal development. It also gives practical advice on how to manage children's mental health and problems like ADHD, dyslexia, autism and depression. The book is timely because of the recent surge in interest of the human mind during the Covid-19 pandemic where there has been a dramatic worldwide increase in mental problems brought about by isolation, economic slowdown, unemployment, and loss of our loved ones.
Includes bibliographical references and index.
Keywords: Child psychology; Child development; Mind and body